Synthesis of knowledge of the plant diet of nectar-feeding bats of México - Ortega-García, Stephanie; Saldaña-Vázquez, Romeo A. (THERYA, 2022)
The interaction between bats and plants is key to the stability of ecosystems and economically important industries, such as tequila and mezcal in México. For these reasons, it is important to determine the current state of knowledge about the plant diet of nectar-feeding bats. In this study, we conducted a systematic review of the literature on plants that have been reported as sources of food for nectar-feeding bats (subfamily Glossophaginae) in México. Based on this information, we identified bat species with the best-documented knowledge of their diet, the most consumed plant genera, and the territories with information gaps in the country. The literature search on the diet of nectar-feeding bats was carried out in the Web of Science database, Google Scholar, and digital collections of universities. We constructed rarefaction curves for bat diet richness, a heat map of the plant genera consumed by each, and a map of food localities in the different biogeographical provinces of México. This information served to explore whether knowledge of the diet of bats was related to variables such as the presence of chiropterophilous plants or the richness of nectar-feeding bats. In México, nectar-feeding bats feed mainly on plants of the genera Agave spp., Pseudobombax spp., and Ceiba spp., which, according to the literature, provide food to more than 75 % of nectar-feeding bats in Mexican territory. Leptonycteris yerbabuenae is the species with the most information on its diet in México, while Lichonycteris obscura is the species with the least information. None of the bat species reached a value greater than 65 % of the expected richness. Localities where the plant diet of nectar-feeding bats has been studied correspond to provinces in the Neotropical region of México. Knowledge about the diet of nectar-feeding bats in México is far from complete. The distribution of diet localities is biased over a large part of its geographic range and is positively correlated with areas with higher nectar-feeding bat species richness.